DYNAMIC AND PUSHOVER ANALYSIS OF MULTI-STOREY REINFORCED CONCRETE BUILDING USING DIFFERENT LOAD DISTRIBUTION PATTERN - Mahmood, Mohamad Najim; Mahmood, Halla Jasem Mohamad (Journal of Applied Engineering Science, 2022)
One of nature’s most dangerous phenomena are earthquakes which cause significant harm to both people’s lives and property. In this study, four alternative approaches are used to demonstrate the distribution of lateral loads and compare its impacts on the results of a non-linear static pushover analysis of a ten-storey reinforced concrete (RC) building and study its response to the impact of an earthquake. In order to determine how the structure would respond to earthquake effects, pushover analysis which is an alternative way of time history analysis was adopted and the predicted results are compared with those of nonlinear time history analysis. Given that the building is situated in an area that is actively experiencing earthquakes and has rocky soil, the distributed lateral force is assumed to be equivalent to the design base shear. The study indicated an almost good suitable fit between two categories of pushover loading methods regarding security of the building, maximum base shear, and maximum displacement. The paper also presents a comparison between the results of nonlinear time history analysis at a particular roof displacement with that of pushover analysis.